Pelatihan Penggunaan Internet Sehat dan Aman untuk Meningkatkan Literasi Digital di Lingkungan Masyarakat - Ardiansyah, Muhammad Ridho; Dahnial, Dahnial (Universitas Pahlawan Tuanku Tambusai, 2025)
Training on healthy and safe internet use is crucial for improving digital literacy in the community by teaching critical thinking, securing personal data, avoiding misinformation and cyberbullying, and using technology productively and ethically. This training covers the basics of ICT, cybersecurity, online privacy, and digital culture, and uses participatory methods such as initial surveys, discussions, and interactive activities to achieve practical understanding. The objectives of this research and the benefits of this training are to improve critical thinking skills, protect oneself from online risks, utilize the internet positively and productively, and create a healthy digital environment. Challenges faced in training on healthy and safe internet use to improve digital literacy in the community include unequal access to technology, low public interest in digital literacy, questionable quality of internet content, lack of understanding of online risks such as cyberbullying and fraud, and difficulties in maintaining personal data privacy online. Furthermore, there are challenges in overcoming internet addiction and ensuring the implementation of digital ethics in online interactions.